2014
DOI: 10.1016/s1995-7645(14)60022-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of infection and molecular confirmation by using ITS-2 region of Fasciola gigantica found in domestic cattle from Chiang Mai province, Thailand

Abstract: These results can be confirmed the Giant liver fluke which mainly caused fascioliasis in Chiang Mai was identified as F. gigantica and specimens were the same as those of F. gigantica recorded in other different countries. Nucleotide sequence of ITS-2 region has been proven as effective diagnostic tool for the identification of F. gigantica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Our results suggest that ITS-1 and ITS-2 sequences might be more useful for distinguishing between closely related taxa belonging to the family Clinostomidae than 28S sequences. This has also been suggested in previous studies (Curran et al 2006;Lotfy et al 2010;Phalee and Wongsawad 2014). The monophyletic origin of Euclinostomum has also been indicated in previous findings (Senapin et al 2014;Caffara et al 2016), as illustrated in ITS2 in the present study but not with other markers.…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that ITS-1 and ITS-2 sequences might be more useful for distinguishing between closely related taxa belonging to the family Clinostomidae than 28S sequences. This has also been suggested in previous studies (Curran et al 2006;Lotfy et al 2010;Phalee and Wongsawad 2014). The monophyletic origin of Euclinostomum has also been indicated in previous findings (Senapin et al 2014;Caffara et al 2016), as illustrated in ITS2 in the present study but not with other markers.…”
Section: Discussionsupporting
confidence: 92%
“…In Thailand, the prevalence rates of fasciolosis in cattle and water buffaloes are estimated to be 52·94–67·27%, with the highest incidences in the North and North-east, and the lowest in the South. It has been reported that the Thailand annual economic loss due to fasciolosis in cattle and buffaloes is estimated around 350–400 million baht (US$10–11 million) owing to a lower nutrition conversion, a decrease in milk production and a reduction in fertility of the animals (Srihakim and Pholpark, 1991; Sukhapesna et al 1994; Anuracpreeda et al 2009 a , 2011, 2017 a ; Phalee and Wongsawad, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Miura et al (2005) reported the absence of heterozygosity in ITS-1 genes, which did not provide any support of gene fl ow among different lineages. Some workers suggested the ITS-2 as effective marker for species identifi cation, phylogenetic relations and developmental stages as well as molecular epidemiology and infection control (Rinaldi et al, 2005;Curran et al, 2006;Bazsalovicsová et al, 2010;Lotfy et al, 2010;Shylla et al, 2011;Ghatani et al, 2012;Phalee et al, 2014;Bian et al, 2013;Portier et al, 2012). In helminth parasites, ITS pseudogenes and mitochondrial genes are present and identifi cation of ITS region is not easy due to non-protein coding nature as compared to mitochondrial genes (Benasson et al, 2001).…”
Section: Resultsmentioning
confidence: 99%